A Victory Tower Built by a Slave: The Chand Minar at Daulatabad in Deccan India - Manohar, Mohit (Muqarnas, 2021)
Abstract The Chand Minar (1446) at Daulatabad Fort is one of the tallest pre-modern stone minarets in the world and has long been recognized as a major work of Indo-Islamic architecture. Yet surprisingly little is known about the building: its iconography and the reason for its construction have not been established; even its height is frequently misreported by half. The present article analyzes the building’s architecture and urban context and critically reads its inscriptions against the Tārīkh-i Firishta (ca. 1610), the main primary text for the history of the medieval Deccan. In so doing, the article demonstrates that issues of race shaped the courtly politics in the Deccan at the time of the minaret’s construction. The Chand Minar was commissioned by Parvez bin Qaranful, an African military slave, who dedicated the building to the Bahmani sultan ʿAla ʾ al-Din Ahmad II (r. 1436–58). The article shows that the building commemorated the role of African and Indian officers in a 1443 military victory of the Bahmani sultanate (1347–1527) against the Vijayanagara empire (1336–1664). The construction of the Chand Minar impressed upon Ahmad II the importance of retaining in his court dark-skinned officers from India and Africa (dakkaniyān) at a time when their standing was threatened by the lighter-skinned gharībān, who had immigrated from the western Islamic regions. The article thus presents a detailed study of an important but neglected monument while shedding new light on racial factionalism in the fifteenth-century Deccan.